Effectiveness of bisoprolol versus selective beta-1 blockers in the management of hypertension: a systematic review and meta-analysis of randomized cross-over trials. (14th October 2021) - Jadhav, U; Ray, S; Bansal, S; Nair, T
Abstract: Background: Cross-over trials carry a higher weightage in choosing a therapeutic agent in clinical practice. A meta-analysis of cross-over trials involving the use of bisoprolol in hypertension (HT) would bring about clarity in positioning this drug. Purpose: The present study aimed to clarify the underlying benefits of bisoprolol in the reduction of blood pressure (BP) in HT patients when compared to selective beta-1 blockers (s-BBs - Atenolol, Betaxolol hydrochloride, Esmolol, Acebutolol hydrochloride, Metoprolol succinate, Nebivolol) by performing a meta-analysis of "cross-over" trials published in literature. Methods: Systematic search was undertaken in PubMed, Embase, Cochrane Library, Clinicaltrials.gov registry, Surveillance, Epidemiology and End Results Program and 12 pharmacovigilance databases. Randomized, cross-over studies published up to October 2019 which compared bisoprolol with other s-BBs in HT patients were evaluated in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A meta-analysis was performed using random effects model in terms of mean difference (MD) and 95% confidence intervals (95% CI) for BP, heart rate (HR) and lipid profile. Results: Nine randomized cross-over studies which compared bisoprolol with other s-BBs (atenolol and nebivolol) were included in this meta-analysis. Bisoprolol reported significant reduction of sitting BP [MD: −3.35, 95% CI: −6.75, 0.05; P=0.05] and reduction of diastolic BP [MD: −2.00; 95% CI: −8.04, 4.04; P=0.52, non-significant] among patients with HT when compared to other s-BBs. Heart rate (HR) decreased significantly among HT patients in bisoprolol group treated for 2 w [MD: −6.00; 95% CI: −11.30, −0.70; P=0.03] when compared to those treated with other s-BBs. Analysis of lipid profile showed non-significant reduction of serum cholesterol [MD: −7.74; 95% CI: −17.18, 1.70; P=0.11] and triglyceride [MD: −26.57; 95% CI: −64.34, 11.20; P=0.17] levels in the bisoprolol group compared to other s-BBs. Bisoprolol treatment for 8 w resulted in a slight but statistically significant change in potassium levels [MD: −0.10; 95% CI: −0.16, −0.04; P<0.01] among HT patients. Conclusion: The results of this meta-analysis reported significant efficacy of bisoprolol on BP and HR in comparison to other s-BBs in a meta-analysis of cross-over trials. Our findings show that use of bisoprolol as a therapeutic option is efficacious and safe compared to other s-BBs in this patient population. Funding Acknowledgement: Type of funding sources: None.